2018
DOI: 10.3389/fimmu.2018.01009
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Overcomes Hepatocellular Carcinoma-Induced NK Cell Dysfunction

Abstract: NK cells have potent antitumor capacity. They are enriched in the human liver, with a large subset specialized for tissue-residence. The potential for liver-resident versus liver-infiltrating NK cells to populate, and exert antitumor functions in, human liver tumors has not been studied. We examined liver-resident and liver-infiltrating NK cells directly ex vivo from human hepatocellular carcinomas (HCCs) and liver colorectal (CRC) metastases, compared with matched uninvolved liver tissue. We found that NK cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 41 publications
10
71
1
Order By: Relevance
“…In line with our preliminary unpublished data, Easom et al [31] recently showed a decreased expression of NKG2D on NK cells derived from HCC tissue compared to matched uninvolved liver tissue. They showed that NKG2D down-modulation depended on contact between NK and HCC cells with consequent internalization of the receptor.…”
Section: Alteration Of the Nkg2d-mica/b Axis In Hccsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our preliminary unpublished data, Easom et al [31] recently showed a decreased expression of NKG2D on NK cells derived from HCC tissue compared to matched uninvolved liver tissue. They showed that NKG2D down-modulation depended on contact between NK and HCC cells with consequent internalization of the receptor.…”
Section: Alteration Of the Nkg2d-mica/b Axis In Hccsupporting
confidence: 89%
“…In the HCC setting, data from mouse models are encouraging, as shown by the inhibitory effect exerted on HCC by an NK cell line transfected with IL-15 [68]. In line with these and other findings recently obtained by Easom and colleagues [31] who showed that IL-15 could restore NK cell activity in HCC, it is possible to envision an immunotherapeutic approach by harnessing NK cell activity with IL-15 for HCC ( Figure 2). Table 1.…”
Section: Nk-based Immunotherapysupporting
confidence: 70%
“…Previous report studied the immune profile of 110 patients with HCC and found that NK cells were abundant in the liver tissues of HCC individuals, with higher number of NK cells being detected in non-tumor liver tissues, than in the intratumoral regions (57). Consistent with this finding, a recent report demonstrated that NK cells were infiltrated in the intratumoral regions of HCC at a lower frequency than in the non-tumor liver tissues (34). Most intratumoral NK cells exhibited CXCR6 + CD69 + liver-resident phenotype (34).…”
Section: Nk Cell Dysfunction In Hcc: Decreased Frequency and Defectivmentioning
confidence: 57%
“…In humans, NK cells normally exist in the liver sinusoids (31). Previous reports have demonstrated that up to 80 percent of intrahepatic NK cells are liver-resident (30,(32)(33)(34)(35)(36). Human liver-resident NK cells are characterized by expression of CXCR6 and CD69, have a distinct transcriptional and functional signature, and display memory-like features (37).…”
Section: Intrahepatic Nk Cells: Liver-resident or Liver-infiltratingmentioning
confidence: 99%
See 1 more Smart Citation